Role of protein C in renal dysfunction after polymicrobial sepsis - Gupta, Akanksha; Berg, David T; Gerlitz, Bruce; Sharma, Ganesh R; Syed, Samreen; Richardson, Mark A; Sandusky, George; Heuer, Josef G; Galbreath, Elizabeth J; Grinnell, Brian W (Journal of the American Society of Nephrology, 2007)
Protein C (PC) plays an important role in vascular function, and acquired deficiency during sepsis is associated with increased mortality in both animal models and in clinical studies. This study explored the consequences of PC suppression on the kidney in a cecal ligation and puncture model of polymicrobial sepsis. This study shows that a rapid drop in PC after sepsis is strongly associated with an increase in blood urea nitrogen, renal pathology, and expression of known markers of renal injury, including neutrophil gelatinase-associated lipocalin, CXCL1, and CXCL2. The endothelial PC receptor, which is required for the anti-inflammatory and antiapoptotic activity of activated PC (APC), was significantly increased after cecal ligation and puncture as well as in the microvasculature of human kidneys after injury. Treatment of septic animals with APC reduced blood urea nitrogen, renal pathology, and chemokine expression and dramatically reduced the induction of inducible nitric oxide synthase and caspase-3 activation in the kidney. The data demonstrate a clear link between acquired PC deficiency and renal dysfunction in sepsis and suggest a compensatory upregulation of the signaling receptor. Moreover, these data suggest that APC treatment may be effective in reducing inflammatory and apoptotic insult during sepsis-induced acute renal failure.